Comparison of the response of two scintillator detectors used in an environmental and occupational radiometric survey during the operation of the Argonauta reactor (Brazilian Journal of Radiation Sciences (BJRS), 2023)
The Argonauta research reactor at the Institute of Nuclear Engineering - IEN operates, under normal conditions, at powers ranging from 1.7 to 340 W, developing activities of a scientific-technological nature in the areas of neutron radiography, radionuclide production and conduction from experimental practices to graduate courses at CNEN research institutions and other Brazilian institutes of science and technology. During some security operations, the presence of investigators, students and/or operators inside and around the main hall of the Argonauta is required. Therefore, it is important to assess normal occupational exposure conditions when the reactor is in critical condition. This makes it possible to verify in greater detail the equivalent doses of ambient gamma radiation contained by the combustion of the fuel element inside the reactor room and in the surrounding areas, according to the Radiation Protection Plan (RPP) of this installation. In this work, a didactic activity was carried out to familiarize the students of the first period of the Master's Course in Nuclear Engineering, at the Military Institute of Engineering, with the procedures involved in the radiometric survey of the free, controlled and subsequent locations of this nuclear installation. This practice aims to identify the doses to which Occupationally Exposed Workers (OEW) and the general public are admitted, verifying compliance with regulatory requirements regarding the monitoring of environmental and local activities, as well as a comparison between the radiation monitors used.